A pricing model to monetize your industrial data - Mendizabal-Arrieta, Gorka; Castellano-Fernández, Eduardo; Rapaccini, Mario (Frontiers in Manufacturing Technology, 2023)
Data monetization has become a relevant aspect of the industrial manufacturing. Consequently, this paper proposes a theoretical framework as well as a mathematical model to price industrial data. For this purpose, three characteristics of the data were considered, i.e. (1) quality; (2) entropy and (3) value. Besides, the role of data marketplace’s players was analyzed. In order to validate the economic equation, a case study was carried out by a Spanish manufacturer.